Penggunaan Media Belajar Ebook Berbasis Proyek pada Pembelajaran Pendidikan Kewarganegaraan - Nastiti, Dian; Triyani, Triyani (Journal of Civic Education, 2025)
This study aims to design and validate a project-based e-book as a learning medium for civic education courses. Employing a Research and Development (R&D) methodology, the research was conducted through ten stages: identifying problems, collecting data, designing the product, validating the design, revising, conducting initial testing, further revisions, field testing, final revisions, and preparation for wider implementation. The research involved students from the Karawitan Music Study Program at the Indonesian Institute of the Arts (ISI) Surakarta. Data collection utilized questionnaires, validation instruments, as well as test and non-test techniques. The results showed that the developed e-book obtained a validity score of 92% from expert validators, classifying it as highly valid. Additionally, effectiveness testing demonstrated that 96% of students successfully completed the learning assessment, confirming the e-book’s high effectiveness as a learning medium. E-books offer a flexible, accessible, and interactive platform for delivering instructional content, particularly in higher education settings, where independent learning and digital resources are increasingly prioritized. The use of project-based e-books can also enhance student engagement and improve critical understanding of civic concepts through contextualized activities. However, this study is limited in scope, having been conducted solely at ISI Surakarta with a relatively small and homogeneous sample. Future research should involve broader participant groups across multiple universities and disciplines to evaluate the e-book’s effectiveness in more diverse academic contexts.